(3GdfXQjs - (3CMeO jhSa(B, (3cdHhfIs; (3eMehO QGaJ SdGeI(B, s ((3YeGf(B:s (3OGQ GdeSjQI(B,s, 2011)
(3ebOeI aj YdeGdJObjb h GfhGY GdJObjb ef YOI fhGMjh NOeGJ GdJhcjO Gdegfj h GdGNWGA h GdZT h ChLg GdJdGYH , OQGSI eObb GdMSGHGJ h GhQGb h edaGJ JObjb GdMSGHGJ , CgOGa hhQI hhSGFd h eSDhdjGJ h GOhGJ GdQbGHI GdOGNdjI h LeY GdCOdI h GdbQGFf aj JObjb GdMSGHGJ h JbQjQ eObb GdMSGHGJ h YdGbI JObjb GdMSGHGJ HYedjI GdQbGHI GdOGNdjI h GdJObjb Ydi GdCUhd GdeJOGhdIs
Keywords: (3GdeMGSHIs; (3eQGLYI GdMSGHGJs